Urinary albumin excretion in rheumatoid arthritis is not associated with markers of vasculopathy in distal microvascular beds. (4th December 2018) - Anyfanti, Panagiota; Triantafyllou, Areti; Gkaliagkousi, Eugenia; Zabulis, Xenophon; Dolgyras, Panagiotis; Galanopoulou, Vasiliki; Aslanidis, Spyros; Douma, Stella
Abstract: Objective: Increased UAE is a marker of generalized vascular damage in high‐cardiovascular risk patients. However, it remains unknown whether it corresponds to a state of diffuse vasculopathy in high‐risk patients with RA. Methods: UAE was estimated in 24‐hour urine samples in RA and non‐RA individuals. Retinal arteriolar and venular diameters were calculated from retinal images with computerized software. SEVR was estimated as an index of microvascular coronary perfusion with applanation tonometry. Dermal capillary density was measured from images obtained with nailfold capillaroscopy, using specifically designed software. Results: In a total of 111 individuals, neither UAE (5.1 [2.8‐10.8] vs 6.5 [3.0‐11.7] mg/24 h) nor prevalence of microalbuminuria (11.0% vs 8.1%) significantly differed between patients (n = 74) and controls (n = 37). In the RA group, UAE was not significantly associated with inflammation, nor with any of the studied microvascular indices of the retinal microvasculature, the coronary microcirculation, and the dermal capillary network. Conclusion: Among RA patients, UAE was not associated with markers of vasculopathy in distal microvascular beds. Increased UAE in RA might be primarily considered as a manifestation of localized, compromised function of the renal microvasculature, rather than a marker of generalized microvascular impairment.